2018
DOI: 10.18203/2320-1770.ijrcog20184942
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of early and delayed cord clamping in term deliveries

Abstract: Background: Timing of clamping of the umbilical cord has always been a debatable issue. Early cord clamping (ECC) is defined as clamping of the cord within 30 seconds of delivery of the baby and delayed cord clamping (DCC) is defined as clamping of the cord between 30 to 120 seconds of delivery. Delayed cord clamping, despite some limitations, is said to be beneficial to the neonate.  A comparative study between ECC and DCC was carried out on a select group of term pregnant women without any high-risk factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…Compared with early cord clamping (ECC), DCC can effectively increase hemoglobin and serum ferritin levels and prevent anemia among newborns [5,[10][11][12][13][14]. The present study confirmed the benefit of DCC among newborns, as evidenced by the significantly increased hemoglobin levels at 24-48 hours of age with DCC at three minutes compared to that with DCC at one or two minutes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Compared with early cord clamping (ECC), DCC can effectively increase hemoglobin and serum ferritin levels and prevent anemia among newborns [5,[10][11][12][13][14]. The present study confirmed the benefit of DCC among newborns, as evidenced by the significantly increased hemoglobin levels at 24-48 hours of age with DCC at three minutes compared to that with DCC at one or two minutes.…”
Section: Discussionsupporting
confidence: 80%
“…However, DCC is associated with a few potential complications, including hyperbilirubinemia and polycythemia. In many trials, more hyperbilirubinemia cases were identified following DCC than ECC [ 8 , 13 , 17 , 18 ]. Consistently, in the present study, bilirubin levels in the DCC at three minutes group were higher than those in the DCC at one and two minutes groups.…”
Section: Discussionmentioning
confidence: 99%
“…The mean total bilirubin level of infants in group with ECC was 2.06 mg/dL and in DCC group it was 4.92 mg/dL ( P value: .003). 14 Same study also found that the mean hematocrit level was significantly higher in the DCC group with the mean of 48.67 (range: 32-71%) in comparison to the ECC group with the mean of 42.36 (range: 30-70%) with P value of .002. In our study, we have found that the increment in phototherapy is increased by 47% in DCC group as compared to ECC group.…”
Section: Discussionmentioning
confidence: 71%